Nikah dengan Lafaz Hibah (Studi Komparatif Antara Jumhur Ulama dan Imam Abu Hanifah) - Muhammad Taufan Djafri; Islahuddin Ramadhan Mubarak; Vaizki M. Rusli (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aims to determine and understand the law of marriage with lafaz grants according to the jumhur of scholars and Imam Abu Hanifah. In this study, the authors used a library research type using a normative juridical approach and comparative analysis. The research results found are as follows; First, a grant-based marriage is not recommended according to the jumhur of scholars because the number of scholars only allows lafaz of marriage with lafaz al-nikah and al-tazwij as usual. Second, a marriage with a grant name may be in the Imam Abu Hanifah mazhab because while it is still in the form of ownership transfer, the name may be used in the implementation of the marriage contract. So the use of lafaz grants in a marriage contract is not allowed in the view of the jumhur of scholars, but it is okay for anyone who wants to use Imam Abu Hanifah's opinion about permitting to use the lafaz grant in a marriage contract, because this is just a difference in fiqh issues that sometimes the scholars differ in interpreting or understanding an argument.